Assessing the Role of Sensitive Attributes in Adversarial Debiasing - Minatel, Diego; Parmezan, Antonio R. S.; Souza, Vinicius M. A.; Rezende, Solange O. (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC); 2025: Anais do XXII Encontro Nacional de Inteligência Artificial e ComputacionalDO - 10.5753/eniac.2025.12452, 2025)
Fairness in machine learning refers to the development of models that do not systematically disadvantage individuals or groups based on sensitive attributes. One commonly adopted principle is fairness through unawareness, which holds that models should not explicitly incorporate sensitive attributes into the decision-making process. However, in some scenarios, such as healthcare, variables like sex and age are essential for accurate diagnoses and prognoses. Previous studies have assessed the influence of including or excluding such information during model training. Nonetheless, they have not considered Adversarial Debiasing, a classification algorithm specifically designed to promote equitable results. To address this gap, we propose a comprehensive empirical analysis to investigate the role of sensitive attributes in this algorithm. We experimentally evaluated Adversarial Debiasing across 20 settings using 23 datasets from varying domains, one predictive performance metric, three group fairness metrics, and a non-parametric statistical test. Our findings indicate that classifiers trained without including sensitive information in the input feature set produce more precise and fairer outcomes.